Integrasi Iman dan Akhlak dalam Pemikiran Said Nursi: Fondasi Moral dalam Kehidupan Modern: The Integration of Iman and Morality in the Thought of Badiuzzaman Said Nursi: The Moral Foundation in the Modern Life - Achmad Dahlan; Didi Darmadi (University of Darussalam Gontor, Indonesia, 2025)
This paper aims to analyze and integrate the concepts of faith (iman) and morality (akhlak) in the thought of Said Nursi, as well as to explore his ideas in depth through a direct study of his works. The main objective is to understand the role of faith as the foundation of morality and how morality serves as a tangible manifestation of faith. This study uses a qualitative research method with a literature review approach. The primary source examined is KulliyÄt RasÄil al-NÅ«r, Said Nursi's masterpiece, along with other supporting literature. The results indicate that, according to Nursi, faith is not merely a belief, but also has a concrete impact on an individual's moral behavior. Good morality reflects true faith, while maintaining a noble character further strengthens one's faith. Furthermore, from an Islamic perspective, morality is not only a social norm but also an act of worship that brings the individual closer to Allah. This study also reveals that, in Nursi's view, excessive materialism and worldly indulgence can weaken faith and corrupt morality. Conversely, good morals bring inner peace and happiness as a result of strong faith. The conclusion of this study emphasizes that faith and morality are two interrelated aspects that cannot be separated in the formation of individuals and the creation of a harmonious society. The integration of the two serves as a critical foundation to face the challenges of modern life.